Infant Pneumococcal Carriage in Belgium Not Affected by COVID-19 Containment Measures - Willen, Laura; Ekinci, Esra; Cuypers, Lize; Theeten, Heidi; Desmet, Stefanie (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus pneumoniae is an important and frequently carried respiratory pathogen that has the potential to cause serious invasive diseases, such as pneumonia, meningitis, and sepsis. Young children and older adults are among the most vulnerable to developing serious disease. With the arrival of the COVID-19 pandemic and the concomitant restrictive measures, invasive disease cases caused by respiratory bacterial species, including pneumococci, decreased substantially. Notably, the stringency of the containment measures as well as the visible reduction in the movement of people appeared to coincide with the drop in invasive disease cases. One could argue that wearing protective masks and adhering to social distancing guidelines to halt the spread of the SARS-CoV-2 virus, also led to a reduction in the person-to-person transmission of respiratory bacterial species. Although plausible, this conjecture is challenged by novel data obtained from our nasopharyngeal carriage study which is performed yearly in healthy daycare center attending children. A sustained and high pneumococcal carriage rate was observed amid periods of stringent restrictive measures. This finding prompts us to revisit the connection between nasopharyngeal colonization and invasion and invites us to look closer at the nasopharyngeal microbiome as a whole.